Regulating banks in central and eastern Europe : through crisis and boom - Spendzharova, Aneta; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
How do bank supervisors strike a balance between market self-regulation and pro-active regulatory intervention? This book investigates the choice of banking supervision approach in four European Union member states from Central and Eastern Europe - Bulgaria, Estonia, Hungary, and Slovenia - after their transition to democracy and market economy.
Keywords: Banks and banking; Political science; Europe -- Politics and government; European Union; Economic policy; Regional economics; Spatial economics